2006
DOI: 10.1007/s11416-006-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Network-level polymorphic shellcode detection using emulation

Abstract: Significant progress has been made in recent years towards preventing code injection attacks at the network level. However, as state-of-the-art attack detection technology becomes more prevalent, attackers are likely to evolve, employing techniques such as polymorphism and metamorphism to defeat these defenses. A major outstanding question in security research and engineering is thus whether we can proactively develop the tools needed to contain advanced polymorphic and metamorphic attacks. While recent result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(146 citation statements)
references
References 31 publications
(41 reference statements)
2
144
0
Order By: Relevance
“…We currently use a value of 32 bytes as the threshold for the minimal length of a shellcode sequence. We found that this value works well in our experiments, and it is also significantly shorter than all Windows shellcode encountered in the wild [26].…”
Section: Checking Strings For Shellcodesupporting
confidence: 62%
See 1 more Smart Citation
“…We currently use a value of 32 bytes as the threshold for the minimal length of a shellcode sequence. We found that this value works well in our experiments, and it is also significantly shorter than all Windows shellcode encountered in the wild [26].…”
Section: Checking Strings For Shellcodesupporting
confidence: 62%
“…More precisely, their prototype implementation identifies long valid sequences of instructions in HTTP requests, thus detecting the NOP sledge that commonly accompanies shellcode. Continuing this work, Polychronakis et al [24,26] proposed to apply lightweight emulation on network data to identify polymorphic shellcode. This approach relies on the so-called GetPC heuristic.…”
Section: Related Workmentioning
confidence: 99%
“…In the past few years, many detection approaches [1], [3], [4], [6], [9] have been proposed. Basically, these methods can be divided into two categories: static analysis [3], [4] and dynamic analysis [1], [6], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Basically, these methods can be divided into two categories: static analysis [3], [4] and dynamic analysis [1], [6], [9]. The core idea of static analysis is to disassemble the network stream and then analyze the code-level patterns that could be signatures obtained from existing shellcode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation